M • e • a • s • u • r • e All Other Opportunities Against These (IEEE Software, 1984)
Abstract This study aimed to determine whether active ischemic preconditioning, incorporating exercise during the reperfusion phases, would enhance Yo-Yo Intermittent Recovery Test Level 2 performance in soccer players. Seventeen male amateur soccer players (24.0±1.8 y) completed three different preconditioning sessions before the Yo-Yo Intermittent Recovery Test Level 2. The ischemic preconditioning protocol consisted of three cycles of 4-minute occlusion (220 mm Hg), followed by 4-minute reperfusion (0 mm Hg) in both thighs (at rest). Active protocols were similar to ischemic preconditioning; however, during reperfusion, participants performed intermittent running (ischemic preconditioning+Yo-Yo Intermittent Recovery Test Level 2) or three-repetition maximum squat repetitions (ischemic preconditioning+SQUAT). We assessed countermovement jump and Yo-Yo Intermittent Recovery Test Level 2 performance, heart rate, muscle oxygen saturation, blood lactate, rating of perceived exertion, and session-rating of perceived exertion. Ischemic preconditioning+SQUAT resulted in a greater Yo-Yo Intermittent Recovery Test Level 2 distance compared to ischemic preconditioning (p=0.02 and effect size=0.3) and ischemic preconditioning+YOYO (p=0.01, effect size=0.2). Countermovement jump performance was affected by condition (p<0.01), with ischemic preconditioning+YOYO presenting higher values compared with ischemic preconditioning (effect size=1.1), although no time effect was observed. No significant differences were observed for muscle oxygen saturation (p=0.09), blood lactate (p=0.32), and rating of perceived exertion/session-rating of perceived exertion (p=0.96); however, the mean heart rate was higher with active reperfusion conditions than ischemic preconditioning. Active reperfusion combined with heavy squat exercise slightly improved high-intensity intermittent running performance in soccer players, while also eliciting higher heart rate responses, which should be considered during training monitoring.